2001
DOI: 10.1046/j.1365-3059.2001.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

The process of antagonism of Sclerotium cepivorum in white rot affected onion roots by Trichoderma koningii

Abstract: Trichoderma koningii (strain Tr5) grew in the epidermal mucilage of onion roots without entering healthy epidermal tissue. When placed on the epidermis of Sclerotium cepivorum‐infected roots, T. koningii colonized epidermal passage cells, with little colonization of other epidermal tissues, then branched and spread throughout the root cortical tissues damaged by enzymes and toxins which diffused ahead of S. cepivorum hyphae, and impeded the path of the infection. When T. koningii colonized infected tissue, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
2
32
0
2
Order By: Relevance
“…Studies showed a variability in root colonization ability of Trichoderma spp., some strains can colonize only some sites located on the roots level (Metcalf and Wilson, 2001), but other can colonize the whole surface of the roots for several weeks (Thrane et al, 1997) or month (Harman, 2000). Trichoderma species showed a widespread capacity to act against pathogens through various mechanisms including antibiosis, mycoparasitism and rhizosphere competence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed a variability in root colonization ability of Trichoderma spp., some strains can colonize only some sites located on the roots level (Metcalf and Wilson, 2001), but other can colonize the whole surface of the roots for several weeks (Thrane et al, 1997) or month (Harman, 2000). Trichoderma species showed a widespread capacity to act against pathogens through various mechanisms including antibiosis, mycoparasitism and rhizosphere competence.…”
Section: Discussionmentioning
confidence: 99%
“…The mycelia of the pathogen then disintegrate suggesting an enzyme action [27,28]. Lorito et al [20], Metcalf and Wilson [29] and Sharon et al [30], demonstrated the possible role of chitinolytic and/or glucanases enzymes in the biocontrol exhibited by Trichoderma. These enzymes function by breaking down the polysaccharides, chitin, and glucans that are responsible for the rigidity of fungal cell walls, thereby destroying cell wall integrity limiting the growth of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The sick plot is repeatedly used for chickpea Fusarium wilt resistance screening experiments. The soil was maintained in paper bags and left to dry at room temperature (25)(26)(27)(28)(29)(30) 0 C).…”
Section: Source Of Pathogensmentioning
confidence: 99%
“…Algumas linhagens são capazes de colonizar apenas regiões específicas das raízes (METCALF; WILSON, 2001), enquanto que outras, denominadas "rizosferacompetentes", colonizam toda a superfície radicular, penetram no espaço intercelular das primeiras camadas da epiderme e permanecem em associação com as raízes por longos períodos (várias semanas ou meses) THRANE;JENSEN, 1997;. Existe ainda outra relação, pouco estudada nesse gênero, em que o fungo se estabelece como endófito, ou seja, ele coloniza não só as raízes, mas também outras partes da planta, como descrito para T. stromaticum, o qual foi observado colonizando o sistema vascular de cacau (EVANS; HOLMES; THOMAS, 2003) e cotilédones de cacau e feijão ; e para as espécies T. harzianum, T. hamatum e T. asperellum que colonizam todas as partes da planta de cacau, desde as raízes até às folhas .…”
Section: Biologia E Estabelecimento Da Interação Com Plantasunclassified
“…Nesse sentido, os métodos que têm se mostrado mais apropriados para essa abordagem são REMI e AMT (BHADAURIA et al, 2009;BASSE, 1999;MICHIELSE et al, 2005b; , 1997;DAVIDSON et al, 2000). Diferentemente da recombinação homóloga na levedura S. cerevisiae, onde cerca de 100 pb de sequência homóloga geralmente é suficiente, fungos filamentosos precisam de pelo menos 1 kb de sequência homóloga, e em alguns casos ainda mais (MICHIELSE et al, 2005a;WILSON;IDNURM;HOWLETT, 2002). Assim, embora essa estratégia seja eficaz para nocautear genes-alvo, a frequência desse evento pode ser muito baixa em situações onde a frequência de integração ectópica (recombinação heteróloga) é alta, dificultando a detecção do mutante de interesse e tornando o processo de seleção bastante laborioso .…”
Section: Principais Mecanismos De Biocontrole De Fitopatógenos E Efeiunclassified